Disciplining Desiring Subjects through the Remodeling of Masculinity: A Case Study of a Chinese Reality Dating Show - Chen, Siyu (Modern China, 2017)
If You Are the One, the most watched dating show in China, caused a heated public debate following its debut in 2010, resulting in two government notices being issued regarding the regulation of dating shows. Using textual and intertextual analysis of the show and the public debate surrounding it, this article scrutinizes the transformation, following government regulation, of the construction of masculinity on the show. Drawing on Lisa Rofel's narrative of "desiring China" and Robert P. Weller's concept of "responsive authoritarianism," this article shows how the tension between the market logic of the Chinese media and their political ownership is played out through the negotiation and mobilization of the meaning of gender. This article therefore also sheds light on larger political, economic, and sociocultural configurations in contemporary China.